2016
DOI: 10.21315/mjms2016.23.6.4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Crocin on 6-OHDA-Induced Oxidative/Nitrosative Damage and Motor Behaviour in Hemiparkinsonian Rats

Abstract: To cite this article: Hosseini M, Rajaei Z, Alaei H, Tajadini M. The effects of crocin on 6-OHDA-induced oxidative/ nitrosative damage and motor behaviour in hemiparkinsonian rats. Methods: Left medial forebrain bundle was lesioned by microinjection of 6-OHDA (16μg in 0.2% ascorbate-saline). Crocin (30 and 60 mg/kg) was injected intraperitoneally three days before surgery until six weeks. Rotational behaviour and biochemical analysis were used to evaluate the effect of crocin in a unilateral 6-OHDA-induced mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In the present study, a microinjection of 6-OHDA into the MFB caused oxidative damage to membrane lipids, as evidenced by decreased total thiol concentrations and increased TBARS levels in the striatum at the end of week six. In line with this, studies have demonstrated that 6-OHDA leads to a reduction in glutathione content and superoxide dismutase and catalase activity, and an increase in lipid peroxidation in the striatum 24,29 .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In the present study, a microinjection of 6-OHDA into the MFB caused oxidative damage to membrane lipids, as evidenced by decreased total thiol concentrations and increased TBARS levels in the striatum at the end of week six. In line with this, studies have demonstrated that 6-OHDA leads to a reduction in glutathione content and superoxide dismutase and catalase activity, and an increase in lipid peroxidation in the striatum 24,29 .…”
Section: Discussionmentioning
confidence: 61%
“…One minute after the injection, ipsi-and contralateral rotations were counted for 30 minutes in a dimly-lit, quiet room. The data were expressed as the net (contralateral minus ipsilateral turns) average rotations per 30 minutes 24 .…”
Section: Apomorphine-induced Rotation Testmentioning
confidence: 99%
“…In 6‐OHDA‐treated mice, crocin (60 mg/kg; i.p. for 6 weeks) significantly reduced the nitrite levels and prevented the nitrosative damage in the striatum ( p < .05; Hosseini et al, 2016).…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, crocin (10 mg/kg) diminished TNF‐α and IL‐6 levels in the striatum of malathion‐treated rats, exhibiting PD‐like behavior (Mohammadzadeh et al, 2018). Nitrite levels in the striatum were drastically reduced after treatment with crocin at a dosage of 60 mg/kg in a unilateral 6‐OHDA‐induced model of PD (Hosseini et al, 2016).…”
Section: Crocin Inhibits Neuroinflammation In Parkinson's Diseasementioning
confidence: 99%